2015
DOI: 10.1364/oe.23.001470
|View full text |Cite
|
Sign up to set email alerts
|

Tb/s physical random bit generation with bandwidth-enhanced chaos in three-cascaded semiconductor lasers

Abstract: We experimentally demonstrate fast physical random bit generation from bandwidth-enhanced chaos by using three-cascaded semiconductor lasers. The bandwidth-enhanced chaos is obtained with the standard bandwidth of 35.2 GHz, the effective bandwidth of 26.0 GHz and the flatness of 5.6 dB, whose waveform is used for random bit generation. Two schemes of single-bit and multi-bit extraction methods for random bit generation are carried out to evaluate the entropy rate and the maximum random bit generation rate. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 34 publications
1
90
0
Order By: Relevance
“…Fast chaotic laser outputs have been used for applications in fast physical random number generation [16][17][18], secure key distribution [19,20], and reservoir computing [21,22]. Figure 1 shows the decision-making scheme based on the TOW method using chaotic temporal waveforms of the semiconductor laser.…”
Section: Tug-of-war Methods Using a Chaotic Semiconductor Lasermentioning
confidence: 99%
“…Fast chaotic laser outputs have been used for applications in fast physical random number generation [16][17][18], secure key distribution [19,20], and reservoir computing [21,22]. Figure 1 shows the decision-making scheme based on the TOW method using chaotic temporal waveforms of the semiconductor laser.…”
Section: Tug-of-war Methods Using a Chaotic Semiconductor Lasermentioning
confidence: 99%
“…It is reported that high-order differential method increases the generation rate to 300 Gb/s 10 whereas the bit-order reversal method along with 8 LSBs sampled at 50 GHz brings up 400 Gb/s rate 11 . Recently, a generation rate of 2.2 Terabit per second (Tb/s) is reached via high-order finite differences pseudo RNG 12 in 2014 while a 1.4 Tb/s physical RNG was reported in 2015 using 2 chaotic data lines sampled at 100 GS/s by 8 bits ADC 13 .…”
Section: Introductionmentioning
confidence: 99%
“…have achieved a 75-Gbit/s RNG rate by utilizing a bandwidth-enhanced chaotic laser, where a cascading optical feedback and injection structure was used to realize a 16-GHz chaotic bandwidth. In 2015, Sakuraba et al 21. have further increased the RNG rate to 1.2 Tbit/s by using a 35.2-GHz bandwidth-enhanced three-cascaded laser structure.…”
mentioning
confidence: 99%
“…By optimizing the post data processing method and enhancing the chaotic bandwidth, the chaos-based RNG rate has already exceeded Tbit/s16171921. However, in order to enhance the RNG rate, merging of two random-bit streams processed by bit-revise and LSBs methods were used in post data processing1921 or only “quasi-physical” random bits could be generated since high-order derivative method was needed to acquire additional valid bits exceeded the raw ADC1617.…”
mentioning
confidence: 99%